The Eschenmoser's Salt as a Formylation Agent for the Synthesis of Indolizinecarbaldehydes and Their Use for Colorimetric Nitrite Detection. Issue 4 (20th December 2022) - Antón‐Cánovas, Teresa; Alonso, Francisco
Abstract: C−H bond formylation is the most immediate way to incorporate the versatile formyl group into (hetero)aromatics. However, the type of reagents and severe conditions involved in the classical formylation methods often curtail their application, especially in the presence of other functional groups. Herein, we present the Eschenmoser's salt, a commercially available (dimethylamino)methylating chemical, as a useful reagent for the C−H formylation of indolizines and other compounds. The method is straightforward and mild, furnishing indolizinecarbaldehydes in modest‐to‐good yields with exclusive and remote regioselectivity. Furthermore, these compounds can be easily transformed into push‐pull dyes and are highly selective in the colorimetric detection of nitrite, a substance extensively employed as preservative in the food industry, the concentration of which is crucial to control to prevent harmful effects in living organisms. The assay is simple, allowing the naked‐eye detection of nitrite in solution or on a cotton swab for a wide range of concentrations. Abstract : We report the unprecedented use of the Eschemoser's salt—a well‐known and commercial reagent for (dimethylamino)methylation reactions—as a formylation agent of indolizines. The method is simple and mild, whereas the classical formylation methods failed. Moreover, some indolizinecarbaldehydes have been transformed into highly conjugated push‐pull dyes and have proven to be selective and sensitive colorimetric anion sensors for nitrite detection.